Industry 4.0 through the lenses of technology, strategy, and organization: A compilation of case study evidence - Demeter, Krisztina; Losonci, Dávid; Marciniak, Róbert; Nagy, Judit; Móricz, Péter; Matyusz, Zsolt; Baksa, Máté; Freund, Anna; Jámbor, Zsófia; Pistrui, Bence; Diófási-Kovács, Orsolya (Vezetéstudomány / Budapest Management Review, 2021)
In the last few years, the management literature has become noisy with Industry 4.0 (I4.0). Although several concepts and typologies intend to make the phenomenon more understandable, these endeavours generally focus on technological aspects or specific issues. Therefore, integrated approaches of the I4.0 transformation on the business side and a comprehensive investigation of this phenomenon on the academic side are still needed. This paper synthetizes the lessons of 15 case studies from five sectors (automotive, FMCG, logistics services, retail, and business services) and places them in a triadic framework of technology, strategy, and organization. The case studies are based on interviews, internal documents and public information. This paper reveals that the analysed companies focus on I4.0 technologies that are substantially related to the development of core activities. Companies in a highly competitive global environment (e.g., automotive industry and business services) are more prepared and progress faster with I4.0 technology implementation.